Photocatalytic Activity of Nanostructured Titanium Dioxide Thin Films - Zdenek Michalcik; Marta Horakova; Petr Spatenka; Sarka Klementova; Martin Zlamal; Nicolas Martin (International Journal of Photoenergy)
The aim of this paper is to investigate the properties and photocatalytic activity of nanostructured TiO2 layers. The glancing angle deposition method with DC sputtering at low temperature was applied for deposition of the layers with various columnar structures. The thin-film structure and surface morphology were analyzed by XRD, SEM, and AFM analyses. The photocatalytic activity of the films was determined by the rate constant of the decomposition of the Acid Orange 7. In dependence on the glancing angle deposition parameters, three types of columnar structures were obtained. The films feature anatase/rutile and/or amorphous structures depending on the film architecture and deposition method. All the films give the evidence of the photocatalytic activity, even those without proved anatase or rutile structure presence. The impact of columnar boundary in perspective of the photocatalytic activity of nanostructured TiO2 layers was discussed as the possible factor supporting the photocatalytic activity.